Improving Students’ Vocabulary Mastery Through Cartoon Movie Clips At Eight Grade Students of SMPN 1 Bulango Utara - Siti Mutmainnah Dauhi; Moon Hidayati Otoluwa; Sri Rumiyatiningsih Luwiti (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The goal of  this research is to find out whether cartoon movie clips can improve students' vocabulary mastery through cartoon movie clips at eight grade students of SMPN 1 Bulango Utara, or not. The sample in this study, were students of class VIII 1 with a total of 31 students at SMP Negeri 1 Bulango Utara in the 2024/2025 academic year. In this study, the method used is a quantitative method in which data is presented in the form of numbers and tested using statistical formulas with the aim of testing the hypothesis that has been previously set. This research design is a pre-experimental design using a one-group pre-test and post-test design in a certain sense this research only uses one group of initial tests and final tests to see changes before and after treatment in one group. Research data were obtained using multiple choice tests as research instruments, then giving pre-test, treatment, and post-test as data collection techniques. Furthermore, the data were analyzed using t-test. The result of this study shows that there is an increase in students' vocabulary after being given treatment using cartoon movie clips. This is shown from the results of the average value of students before being given treatment or pre-test of 32.93, while the average value after being given treatment or post-test of 65.5. It can be concluded that cartoon movie clips can improve students' English vocabulary and the hypothesis of this study is accepted.